POTRET GEOGRAFIS KEMISKINAN DI PROVINSI BENGKULU: KOMPARATIF KEMISKINAN WILAYAH UTARA DAN SELATAN - Rihan Ifebri; Reflis Reflis; Ellys Yuliarti; Sriyoto Sriyoto; Osronita Osronita (Jurnal Azimut, 2023)
Multidimensional poverty research was carried out in districts/cities located in the coastal area of ??Bengkulu Province. This research aims to identify the intensity of poverty, identify multidimensional poverty, and identify the level of poverty deprivation in districts/cities in the coastal areas of Bengkulu Province. This research uses secondary data from the Central Statistics Agency (BPS) of Bengkulu Province in the form of microstatistical data, namely National Socio-Economic Survey (SUSENAS) pooled cross-section data with a survey wave period of 2022. The method used is the Multidimensional Poverty Index (MPI) method. modified from Alkire and Foster. The results of the research show that the intensity of multidimensional poverty in the northern region, namely the Muko-Muko district (15.28%) is lower than in the southern region, namely the Kaur district (37.16%). The Multidimensional poverty rate (M) in the Northern region of Bengkulu Province, namely Muko-Muko Regency, is smaller (6.16%) compared to the Southern region of Bengkulu Province, namely Kaur Regency (16.98%). Household deprivation status according to multidimensional poverty indicators, namely the number of years of schooling, potable water, and then the indicators of household calorie consumption and household protein consumption which contribute a lot to multidimensional poverty in the Northern region of Bengkulu Province, namely Muko-Muko Regency and the Southern Region of Bengkulu Province, namely Kaur District.